Bony Remodeling of Adolescent Displaced Clavicle Fractures: A FACTS Study. Issue 4 (March 2023) - Pennock, Andrew T.; Bastrom, Tracey P.; Boutelle, Kelly E.; Carroll, Alyssa N.; Edmonds, Eric W.; Nepple, Jeffrey J.; Polinsky, Samuel G.; Spence, David D.; Perkins, Crystal; Willimon, Samuel C.; Bae, Donald S.; Busch, Michael T.; et al.
Background: Bony remodeling of displaced clavicle fractures in adolescents remains poorly understood. Purpose: To evaluate and quantify clavicle remodeling in a large population of adolescents with completely displaced fractures, which were treated nonoperatively, to better understand the factors that may influence this process. Study Design: Case series; Level of evidence, 4. Methods: Patients were identified from the databases of a multicenter study group investigating the functional outcomes of adolescent clavicle fractures. Patients between the ages of 10 and 19 years with completely displaced middiaphyseal clavicle fractures that were treated nonoperatively and who had further radiographic imaging of the affected clavicle at a minimum of 9 months from initial injury were included. Fracture shortening, superior displacement, and angulation were measured on the injury and final follow-up radiographs using previously validated techniques. Furthermore, fracture remodeling was classified as complete/near complete, moderate, or minimal, using an original classification system found to have good to excellent reliability (interobserver reliability = 0.78, intraobserver reliability = 0.90). Classifications were subsequently analyzed quantitatively and qualitatively to determine the factors associated with deformity correction. Results: Ninety-eight patients (mean age, 14.4 ± 2.0 years) were analyzed at a mean radiographic follow-up of 3.4 ± 2.3 years. Fracture shortening, superior displacement, and angulation significantly improved during the follow-up period by 61%, 61%, and 31%, respectively ( P < .001). Furthermore, while 41% of the population had initial fracture shortening >20 mm at final follow-up, only 3% of the cohort had residual shortening >20 mm. Fracture remodeling was found to be associated with follow-up time; those with longer follow-up time demonstrated more remodeling ( P = .001). Eighty-five percent of patients aged <14 years and 54% of patients aged ≥14 years at time of injury with a minimum follow-up of 4 years underwent complete/near-complete remodeling. Conclusion: Significant bony remodeling occurs in adolescent patients with completely displaced clavicle fractures, including older adolescents, and appears to continue over longer time intervals, even beyond the adolescent years. This finding may help explain the low rate of symptomatic malunions in adolescents, even in severely displaced fractures, and particularly when compared with rates reported in adult studies.